MODEL BIMBINGAN PENGEMBANGAN UNTUK MENINGKATKAN KEMATANGAN KARIER MAHASISWA - Fadhilah, Siti S; Natawidjaja, Rochman (PAEDAGOGIA, 2010)
The aims of this research are (1) to design a model of development guidance toimprove the student's career maturity, and (2) to find out the effectiveness of a such model.This research is research and development which use qualitative and quantitativeexploratory mixed methods implementing an experimental with pretest–posttest controlgroup design. It was carried out through the following phases: (1) reviewing relatedtheories and assessing the students' needs; (2) designing the hypothetical model ofdevelopment guidance; (3) validating the model by a number of experts, practitioners,and several students; and (4) trying out in the field which involved a number of samples ofthe research to find out the effectiveness of the model. The research used a clustersampling technique to determine the samples. The samples were 120 students of theexperimental group and 116 ones of the control group. The data were gathered throughinterview, questionnaire, and career maturity measurement tools of Form 1 and Form 2.The results of the analysis show that according to the experts' and practitioners' assessment,the designed model of the development guidance is feasible to be implemented, itmeans that the designed model has fulfilled such required aspects such as contentvalidity, language, and writing, consisting of the guidance guidelines as well as theguidance materials used by the counselors to give guidance to the students. Results ofexperiment show that in experimental group, student's attitude and student's competencefor career are very significant. It means that by giving treatment of guidance there is avery significant difference between pretest and posttest. In control group, student'sattitude and competence for career are noteworthy. It means that without treatment ofguidance there is an important difference between pretest and posttest, but slightdifference. Based on the series of phases, the research reveals that the designed model ofdevelopment guidance is effective to improve the student's career maturity.